2009
DOI: 10.3319/tao.2008.04.24.02(f3c)
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Electron Density Concurrently Derived by TIP and GOX of FORMOSAT-3/COSMIC

Abstract: AB STRACTThe tiny ion o spheric pho tom e ter (TIP) and GPS occultation ex per i ment (GOX) onboard FORMOSAT-3/COS MIC (F3/C) are em ployed to mea sure the OI 135.6 nm in ten si ties in the na dir di rec tion and the to tal elec tron con tent (TEC) be tween the F3/C and GPS sat el lite in the ion o sphere, re spec tively. Due to its very high sen si tiv ity ~600 counts/Ray leigh and rather nar row na dir point ing 3.8° cir cu lar field-of-view, the TIP pro vides ac cu rate char ac ter iza tion of ion o spheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition to the RO electron density profiles, the 135.6 nm airglow measurements by TIP have also been used in examining the ionospheric structures. Simultaneous observations of F3/C TIP and GOX have been used to conduct a full space-based (without ground-based receiving stations) ionospheric tomography (Hsu et al 2009) and to study ionospheric auroral oval development (Tsai et al 2010). TIP measures nadir integrated OI 135.6 nm intensities, whereas GOX observes the line-ofsight TEC between the F3/C and GPS satellite.…”
Section: Integrated Gox and Tip Observationsmentioning
confidence: 99%
“…In addition to the RO electron density profiles, the 135.6 nm airglow measurements by TIP have also been used in examining the ionospheric structures. Simultaneous observations of F3/C TIP and GOX have been used to conduct a full space-based (without ground-based receiving stations) ionospheric tomography (Hsu et al 2009) and to study ionospheric auroral oval development (Tsai et al 2010). TIP measures nadir integrated OI 135.6 nm intensities, whereas GOX observes the line-ofsight TEC between the F3/C and GPS satellite.…”
Section: Integrated Gox and Tip Observationsmentioning
confidence: 99%
“…Oxygen emissions at 630.0 nm and 777.4 nm have been used to estimate peak electron density as well as F peak altitude [ Tinsley and Bittencourt , 1975; Chandra et al , 1975; Sahai et al , 1981]. However, OI 135.6 nm emission is the one widely used in satellite experiments [ Hicks and Chubb , 1970; Barth and Schaffner , 1970; Mende et al , 2000; Sagawa et al , 2003; Christensen et al , 2003; Kil et al , 2004; Dymond et al , 2000, 2009; Hsu et al , 2009]. The nighttime OI 135.6 nm emission is mainly through the radiative recombination process, and its intensity is hence related to the square of the electron density [ Hanson , 1969; Tinsley and Bittencourt , 1975; Meier , 1991].…”
Section: Introductionmentioning
confidence: 99%
“… DeMajistre et al [2004] used the Global Ultraviolet Imager (GUVI) 135.6 nm limb images onboard the Thermosphere, Ionosphere, Mesosphere Energetics and Dynamics (TIMED) satellite to retrieve nighttime electron density profiles. Recently, Dymond et al [2009] and Hsu et al [2009] reported the electron density profiles using the Tiny Ionospheric Photometer (onboard FORMOSAT‐3 satellites) measurements. The methods followed in these inversions provide the electron density profiles based on a forward model used to simulate the observed data, and are subject to the constraints inherent in the algorithms, and the assumptions and initial conditions involved.…”
Section: Introductionmentioning
confidence: 99%
“…The TIP is a nadir viewing compact, high sensitive UV photometer onboard the F3/C satellites that measures the integrated OI 135.6 nm intensity along the line-of-sight Hsu et al 2009). TIP can detect even minute intensity variations with a very high sensitivity of about 500 counts second -1 Rayleigh -1 .…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Observations from this track will hence give the airglow signature without any contamination to the detector itself. Note that the ISUAL observations include an upper O( 1 D) layer and a lower OH(9 -3) layer in the limb images (Rajesh et al 2009;Nee et al 2010). The strong O( 1 D) enhancement between 30° -35°S latitudes, occurring below the tangent altitude of 200 km, most likely results from the energetic particle contribution to the emission.…”
Section: Discussionmentioning
confidence: 97%